PENGARUH PEMBERIAN DOSIS Trichoderma sp DAN DOSIS PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (Capsicum frutescens L.) - I Made Indra Agastya; Roimil Latifa; Wahyu Fikrinda; Stefanus jappa (BUANA SAINS, 2022)
This research aimed to determine the effect of Trichoderma sp dosage and cow manure dosage on the growth and yield of cayenne pepper. The research used a randomized block design with three replications. The factors studied were the dose of Trichoderma with three levels, namely T0 (Trichoderma dose of 0 g / polybag), T1 (Trichoderma 0.5 g / polybag), and T2 (Trichoderma 1 g / polybag), as well as the dosage factor of cow manure with four levels are P0 (cow manure dose 0 g / polybag) P1 (cow manure 125 g / polybag), P2 (cow manure 250 g / polybag) and P3 (cow manure 375 g / polybag). The variables studied were plant height, stem base diameter, number of leaves, number, number of fruits, the weight of fruit crops, and production of tonnes/ha. The results showed that the treatment dose of Trichoderma T0 (without Trichoderma), T1 (Trichoderma dose of 0.5 g / polybag), and T2 (Trichoderma 1 g / polybag) had no significant effect on all plant parameters, while the dose treatment of cow manure in treatment P0 (without cow manure) significantly different from treatment P1 (cow manure 125 g / polybag), P2 (cow manure 250 g / polybag), and P3 (cow manure 375 g / polybag). There was no interaction between doses of Trichoderma with the dose of cow manure on the growth and yield of cayenne pepper